Studies on the Knowledge, Attitude and Perception (KAP) for Malaria among Patients Attending PHCs in Jos, Jos-North LGA, Plateau State - Nwibari, B. M. W.; Shafa, A. B.; Joachim, B. N.; Luka, I.; Ushie, B.; Moses, J.; Nanvyat, Nannim (Sahel Journal of Life Sciences FUDMA, 2024)
Malaria is still a major public health challenge in Nigeria and other sub-Saharan and tropical countries. The study is aimed at determining the Knowledge, Attitude, and Perception (KAP) of malaria among 200 in and outpatients attending selected Primary Health Centers (PHC) in Jos North Local Government Area (LGA), Plateau State, Nigeria. A hyperendemicity 300(52%) with intense densities across those examined individuals computing across sex, age, and occupational groups at no significant statistical differences (PD 0.05), even though there were significant statistical differences (P<0.05) between the PHCs, Dogo-Agogo, Nasarawa, and Apata. It became necessary to analyze their inclinations to these results through only 200 of the 300 in and outpatients, alongside their specialized KAP using well-designed questionnaires. Their Yes, No, and Uncertain responses collated speak for the reasons for the hyper-endemicity and consequential high densities across the sociological indexes examined for the disease in the study. Adequate attention to discouraging dwellers of the study location from complacencies to adherences towards medical experts' prescribed treatments, and researchers commended preventive measures away from ignorance of the debilitating and disgusting mortality and inability effects impacted on their lives by the hypoendemic parasites through body exposures to these transmitters, to better their general health status, and beyond, became measure advocacy, by well-meaning individuals, non-governmental and governmental organizations and agencies, be they local, national and international.